A study on postnatal care and its correlates among recently delivered women visiting to BRD medical college Gorakhpur - Tiwari, Harish Chandra; Gupta, Sudhir Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Postnatal care is crucial in maintaining and promoting the health of the woman and the newborn baby. Despite the known benefits of the postnatal care, there are many access and utilization barriers to care. The present study was conducted on postnatal care and its correlates among recently delivered women visiting to BRD Medical College Gorakhpur. Methods: For present cross-sectional study recently delivered women (RDW) defined as a post natal woman who had a baby between two months to six months of age at the time of data collection were taken as the study subjects. Complete post natal care was considered if RDWs had received post natal check-up (Post natal day -1, day-3, day-7,) along with immunization of child with BCG, OPV and three doses of DPT/Pentavalent vaccine. Sample size was calculated as 275 by using the formula 4PQ/L2 with an allowable error (L) of 20% including 10% extra for non/incomplete responders. The proportion of women receiving postnatal care was considered as 50.0% as by this proportion maximum sample size is arrived. Results: A total of 269 recently delivered women (RDW) were taken as the study subjects. They belonged to age group 19-29 year (Mean age 23.7±6.7 year), either educated up to 12th standard and only few were graduate or post graduate. Majority of them belonged to middle or lower middle class. Conclusions: Postpartum care utilization was associated with socioeconomic status, antenatal care received or not, planned pregnancy or not. Interestingly, access to care was not perceived as a top reason for not obtaining PPC.